Theoretical and simulation classes in the emergency nursing curriculum in Cape Verde: Effect on the self-confidence to intervene in emergencies - Martins, José Carlos Amado (2014)
Background/Objective: Self-confidence is an attitude often associated with repeated experiences and with the realistic perception of individual weaknesses and strengths. It is not the same as competence but, with a view to a safe and timely intervention in the emergency context, it is necessary that nurses feel confident in their ability to intervene appropriately. In the context of simulation, the students' self-confidence is an important outcome that needs to be evaluated. Objective: To evaluate the effect of theoretical and simulation classes on the nursing students' self-confidence. Methods: Quasi-experimental study, without control group, with evaluation at three moments: before the classes, after the theoretical classes (40 hours) and after the simulation classes (25 hours). Questionnaires with the Portuguese version of the Self-confidence Scale were applied to 59 nursing students in two courses, in 2011 (25 students) and 2012 (34 students). All the students were taking the third year of the nursing undergraduate program. Formal and ethical principles were followed. Results: The mean global self-confidence score corresponded to 2.35 on the first evaluation, increasing to 3.07 on the second and 3.34 on the third. The t-test reveals that these differences are highly significant (p < .001). The individual analysis of each dimension (neurological, breathing and circulation) reveals similar and statistically highly significant improvements. Conclusions: The classes were effective to improve the level of self-confidence. Simulated practice is a good strategy to improve the confidence to intervene in an emergency situation.